Temná strana krále kaktusů: Co MAXQDA neumí a co s tím dělat - Ondřej Hejnal (AntropoWebzin)
Without a doubt, MAXQDA, the leading CAQDAS (software), is one of the most useful and commonly used tools for qualitative data analysis. Despite this and, in a sense, outside the common praise “the King of the CAQDAS”, the aim of this methodological paper is to present a variety of troubles (and their solutions) associated with the processing of a dataset with more than 90,000 media messages in MAXDictio (MAXQDA addon). Going in steps, I will demonstrate the phases of data import, categorization of data, autocoding of sentences, word frequencies, selectionofkeywords,dictionary-makingandananalysis of co-occurrences. In addition to MAXQDA, the article will mention some minor applications/software, potentially very handy for the diverse forms of computerassisted text analysis (CATA). Accordingly, what are the limits of MAXQDA? And if exceeded, what are the solutions? And what other software can be (or have to be) used with MAXQDA.